(untitled) (World Bulletin of Public Health, 2026)
One of the most important goals of the international public health system is the elimination of preventable infant and perinatal mortality (WHO, 2014) [1]. Key factors in the development of these changes include intrauterine fetal hypoxia and neonatal asphyxia, both acute and chronic. The adrenal gland is a key organ involved in the stress response. Despite this, data on the of the adrenal glands in acute and chronic hypoxia during the perinatal period remain incomplete and fragmented